A Case of Myxoid Liposarcoma of the Retroperitoneum: A Challenging Tumour for Diagnosis and Treatment. (12th June 2014) - Grasso, Emanuele; Marino, Fabio; Bottalico, Michele; Simone, Michele
Abstract : Retroperitoneal sarcomas are rare neoplasms that account for only 1%-2% of all solid tumors and liposarcomas represent the most frequent histological type. We describe the case of a 44-year-old female with a retroperitoneal myxoid liposarcoma of 22 × 19 × 8 cm in size. The only symptoms were persistent pain and progressive tenderness of the abdomen lasting for two months. The mass was radically excised during laparotomy. CT and MRI were useful to clarify the site of origin of the tumor, relationships with other organs, and planning surgery but final diagnosis was based on histological findings. Here we review the literature about the challenging diagnosis, treatment, and prognostic factors of this disease.